2019
DOI: 10.1371/journal.pone.0211577
|View full text |Cite
|
Sign up to set email alerts
|

HPV-driven oropharyngeal squamous cell cancer in Croatia — Demography and survival

Abstract: ObjectivesHead and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide. Main HNSCC risk factors are tobacco, alcohol, and high-risk human papillomavirus (HPV). HPV+ oropharyngeal squamous cell cancer (OPSCC) usually have different etiology, increasing incidence and often show an improved survival when compared to HPV-negative cases. The objective of the current study was to retrospectively examine the influence of HPV on the survival of OPSCC patients in a non-Western population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
(73 reference statements)
1
16
0
Order By: Relevance
“…HPV-positivity according to oropharyngeal subsites was reported in 19 studies (48,250). Ten studies reported the highest HPV+ rate in palatine tonsillar squamous cell carcinoma (TSCC) ( n = 47,690) [ 4 , 19 , 20 , 21 , 28 , 32 , 33 , 34 , 35 , 36 ], and three reported the highest HPV+ rate in base of tongue squamous cell carcinoma (BTSCC) ( n = 2 51) [ 29 , 37 , 38 ].The proportion of HPV-positivity among patients with TSCC varied from 15% to 86%, among patients with BTSCC from 1% to 82%, and for other oropharyngeal locations from 1% to 100%, Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…HPV-positivity according to oropharyngeal subsites was reported in 19 studies (48,250). Ten studies reported the highest HPV+ rate in palatine tonsillar squamous cell carcinoma (TSCC) ( n = 47,690) [ 4 , 19 , 20 , 21 , 28 , 32 , 33 , 34 , 35 , 36 ], and three reported the highest HPV+ rate in base of tongue squamous cell carcinoma (BTSCC) ( n = 2 51) [ 29 , 37 , 38 ].The proportion of HPV-positivity among patients with TSCC varied from 15% to 86%, among patients with BTSCC from 1% to 82%, and for other oropharyngeal locations from 1% to 100%, Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, HPV is known to be more associated with oropharyngeal tumors than oral cavity cancerogenesis [ 26 ]. Another possible explanation is the particularity of the Croatian population where smoking and drinking are almost equally present in HPV positive and HPV negative OPSCC patients shown in our previous study [ 27 ]. On the other hand, the study of Lechner et al with Infinium HumanMethylation450 BeadChips (Illumina) showed unsupervised clustering over the methylation variable positions of samples in accordance with the HPV status.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, HPV is known to be more associated with oropharyngeal tumors than oral cavity cancerogenesis (37). Another possible explanation is the particularity of the Croatian population where smoking and drinking are almost equally present in HPV positive and HPV negative OPSCC patients shown in our previous study (38). On the other hand, the study of Lechner with the clinical outcome in glioblastoma multiforme patients (40).…”
Section: Discussionmentioning
confidence: 82%